Analysis of a Possible Overreaction in Returns of Tech Stocks during 2020 US Presidential Election - Perlác, Radovan (2022)
The purpose of this thesis is to analyze a possibility of an overreaction in technology stocks during the period of the 2020 US presidential election in the context of behavioral finance. Thesis is divided into two parts, one theoretical and one experimental. The theoretical part focuses on explaining the theory of behavioral finance, what it stands for, and the reasons for its founding. Experimental part first outlines the methodology of event studies, which is then used in order to derive and interpret our z-score statistical test results. In conclusion, we found no overreaction when testing longer sequences around the election date. However, between individual days, we did manage to find two statistically significant overreactions on November 9 & 10, right after the election results had been released. These overreactions were negative, portraying the pessimistic sentiment of tech investors in consequence of the election results.